2005
DOI: 10.1029/2005gl023740
|View full text |Cite
|
Sign up to set email alerts
|

One more step toward a warmer Arctic

Abstract: This study was motivated by a strong warming signal seen in mooring‐based and oceanographic survey data collected in 2004 in the Eurasian Basin of the Arctic Ocean. The source of this and earlier Arctic Ocean changes lies in interactions between polar and sub‐polar basins. Evidence suggests such changes are abrupt, or pulse‐like, taking the form of propagating anomalies that can be traced to higher‐latitudes. For example, an anomaly found in 2004 in the eastern Eurasian Basin took ∼1.5 years to propagate from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
226
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 289 publications
(245 citation statements)
references
References 19 publications
15
226
1
Order By: Relevance
“…IOPAS investigations show that the main cause of the increase in northward volume and heat transport was the intensification of the northward currents. The results from the mooring array in Fram Strait confirm that such intensification took place in 2005(Schauer et al, 2008.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…IOPAS investigations show that the main cause of the increase in northward volume and heat transport was the intensification of the northward currents. The results from the mooring array in Fram Strait confirm that such intensification took place in 2005(Schauer et al, 2008.…”
Section: Discussionsupporting
confidence: 64%
“…The IOPAS investigation shows that the intense activity of the western WSC branch, especially the great anticyclonic eddies carrying large heat anomalies, was very important as regards the increase in northward transport and raising the AW temperature in 2005(Walczowski and Piechura, 2007. The eddies were much larger than the frontal mesoscale features usually observed (Piechura and Walczowski, 1995).…”
Section: Temporal Variability In Wsc Propertiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Lags in water properties occur in part because, even if circulation remained constant, the transit times required to move a changed water property through the basin are measured in years [Polyakov et al, 2005]. For example, a 7-year lag between Atlantic water temperature rise in the Makarov Basin and that initially seen at the North Pole was found by Kikuchi et al [2005].…”
Section: Discussionmentioning
confidence: 99%
“…Atlantic Water (AW) entering the Arctic via the Barents shelf and West Spitzbergen Current (WSP) have warmed since the early 1990s, producing temperature anomalies in the Nansen Basin of roughly 118C in 2004 (Polyakov et al 2005). The increased penetration of AW caused the cold halocline (CHL) to retreat from the Amundsen Basin to the Makarov Basin in the mid-1990s (Steele and Boyd 1998), although measurements showed that it had returned to the Amundsen Basin in 2001 (Bjö rk et al 2002).…”
Section: Introductionmentioning
confidence: 99%